Nondigital skin ulcers in systemic sclerosis: A neglected entity - Benzeeta Pinto; Ramya Janardana; Sowmya Kaimal; B Sheba Charles; K N Sangeeta; Jasmine Mathew; Kodishala Chanakya; John Michael Raj; Vineeta Shobha (Indian Journal of Rheumatology)
Background: Skin ulcers (SUs) are a common and difficult to manage problem in systemic sclerosis (SSc) and can be broadly classified into two types: digital ulcers (DUs) and non-DUs. Objective: The objective of this study was to analyze prevalence, associated factors, and response to therapy for non-DU. Patients and Methods: All patients with SSc who fulfilled the 2013 ACR/EULAR criteria were included in the study. SUs were divided into DU and various types of non-DU (SU on bony prominences, SU on calcinosis, SU on lower limbs, and SU with gangrene). Results: We included 146 patients with SSc (83.6' females) with a median follow-up of 20.5 months (interquartile range: 52). Eighty-four patients (57.5') had at least one episode of DU. Recurrent DUs despite vasodilators were seen in 36 (24.7') patients. Thirty-four patients (23.3') had non-DU. The most common type of non-DU was SU of lower limbs (23), followed by SU on bony prominences (19). The most common ulcer site was on the malleoli in the lower limbs and elbow in the upper limbs. Most of the ulcers healed in 3–6 months. Three patients developed osteomyelitis. The presence of non-DU was associated with longer duration of disease (P = 0.0009), occurrence of DU (P = 0.011), presence of gangrene (P < 0.001), or calcinosis (P < 0.001), and higher modified Rodnan skin score (P = 0.0013). Conclusion: Non-DUs were found in a quarter of patients with SSc. They are associated with advanced disease and vasculopathy. There is an unmet need to incorporate non-DU in clinical trial outcomes and address them in patient management guidelines.